2014
DOI: 10.1177/0021998314533361
|View full text |Cite
|
Sign up to set email alerts
|

Rice husk flour biocomposites based on recycled high-density polyethylene/polyethylene terephthalate blend: effect of high filler loading on physical, mechanical and thermal properties

Abstract: Biocomposites of recycled high-density polyethylene (rHDPE)/recycled polyethylene terephthalate (rPET) matrices with a high loading of rice husk flour (RHF) were fabricated through a two-step extrusion. The use of ethylene-glycidyl methacrylate (E-GMA) copolymer improved the compatibility of the immiscible rHDPE/rPET blend. Maleic anhydride polyethylene (MAPE) was used as a coupling agent to increase the adhesion of the fibre–matrix interface. In this study, the effect of natural fibre loadings on rHDPE/rPET b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
33
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 53 publications
5
33
0
2
Order By: Relevance
“…As the RH content increased in the composite materials, To and Tm increased up to 46.5 °C and 14.3 °C, respectively, in contrast to the neat rTPB. These observations indicated that the addition of the RH filler had improved the thermostability of the rTPB matrix, as reported in the authors' previous study on an untreated RH/polymer blend (Chen et al 2014a). Above Te, it was found that the remaining residual content gradually increased with the RH content because of the high silica content in the RH, which formed silica ash upon heating.…”
Section: Thermal Degradation and Stabilitysupporting
confidence: 82%
“…As the RH content increased in the composite materials, To and Tm increased up to 46.5 °C and 14.3 °C, respectively, in contrast to the neat rTPB. These observations indicated that the addition of the RH filler had improved the thermostability of the rTPB matrix, as reported in the authors' previous study on an untreated RH/polymer blend (Chen et al 2014a). Above Te, it was found that the remaining residual content gradually increased with the RH content because of the high silica content in the RH, which formed silica ash upon heating.…”
Section: Thermal Degradation and Stabilitysupporting
confidence: 82%
“…RH is a lignocellulosic material that is renewable and abundantly available in Malaysia. The raw RH consists of 25 to 35% cellulose, 18 to 21% hemicellulose, 26 to 31% lignin, 15 to 17% silica, 2 to 5% solubles, and 7.5% moisture content (Chen et al 2015b). RH has low density, high specific strength and modulus, and is biodegradable, tough, resistant to weathering, and makes final products cheaper if it is incorporated into composites compared to other fibers (Zhao et al 2009;Kwon et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…There is still a significant of amount of plastics end up in landfill despite the recycling capacity for plastic wastes have been progressively increased [1]. In Peninsular Malaysia (population of 28.45 million inhabitations in 2010), the total amount of municipal solid waste produced has increased from 19,100 tonnes per day in 2005 to 21,100 tonnes per day in 2010 and plastic wastes account for 24% of them [2]. In view of environmental concern, plastic waste recycling not only conserves both virgin materials and energy but also provides a solution to plastic waste disposal [3].…”
Section: Introductionmentioning
confidence: 99%